INDUKSI POLIPLOIDI TANAMAN KANGKUNG (IPOMOEA AQUATICA FORSSK.) KULTIVAR SALINA IN VITRO DENGAN ORYZALIN - Rahmi, Putri; Witjaksono, Witjaksono; ratnadewi, diah (Perhimpunan Biologi Indonesia, 2019)
ABSTRACTWater spinach is a vegetable plant consumed by people all over the world. Its small morphology requires improvement to increase the size and productivity. An alternative way to do that is by increasing the ploidy of its chromosome. This paper describes in vitro induction of polyploidy of water spinach. Inoculum of in vitro seedling, in vitro shoots and nodal stem segments were immersed in MS solution containing oryzalin at concentrations of 0.00, 1.25, 2.50, 3.75 and 5.00 µM with immersion duration of 4, 8 and 24 hours. Oryzalin treatments reduced the growth variables of the in vitro shoots of all inocula tested, compared to control of no oryzalin treatment. On immersion of 24 hours and high concentration of 5.00 µM, many inoculum failed to grow to the third passage of subculture. The best growth of in vitro shoot to the third passages occurred in the treatment combination of oryzalin 1.25 µM-8 h immersion and 2.50 µM-4 h immersion for seedling inoculum, treatment combination of 3.75 µM-4 h immersion for shoot tip inoculum and 1.25 µM-4 h immersion for nodal stem segment, compared to other treatments. Analysis of flow cytometry on 41 leaf samples from oryzalin treatment derived shoots showed 14.63% tetraploid, 36.59% mixoploid and 48.78% diploid. The efficiency of tetraploid formation reached 60%, provided only by the treatment of oryzalin 1.25 µM-8 h on seedling segments inoculum. Tetraploid shoots need to be proliferated, acclimatized, grown into planting materials and planted for agronomical analysis to provide evidence whether or not tetraploid water spinach is viable for commercial cultivation.